Sistem Informasi Wisata Edukasi Museum Daerah Sambas Dengan Deteksi QR Code Berbasis Web - Sonty Lena; Robindra Robindra (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The Sambas Regional Museum is a museum owned by the government of Sambas Regency, West Kalimantan, which acts as an educational center for the community. Data management in the museum still uses a conventional system, namely by recording it in a book as well as recording visitor data. So that information cannot be conveyed precisely and quickly and lacks attractiveness in its presentation. With the development of a web-based museum educational tourism support information system, it can facilitate the management of collection object data, visitor data, and the dissemination of information that can be accessed online. The design of the Sambas Regional Museum Educational Tourism Support Information System utilizes QR Code technology, which in its development uses the prototyping method and the Unified Modeling Leanguage design model. PHP as a programming language and uses MySQL as a database. The results of this study are web-based applications that can be used as education such as online recognition of museums and their collection objects, as well as facilitating museum managers in storing stores, returning collectibles, and visitor data by utilizing QR Code security so that it is hoped that this will make it easier to introduce the Sambas Regional Museum to society.